The City's Representative Meaning in Samosir's branding “Beautiful Country Pieces of Heaven” in the Heartbeat of Toba Film from the Ministry of Tourism - Riko Andika Rahmat Pohan; Samerdanta Sinulingga (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to describe the film The Heart of Toba showing the socio-cultural conditions of the Toba Batak people, especially in Samosir Regency. In the film The Heart of Toba, there are interesting polished images, and the creation of a light plot in capturing the reality of the life of the Toba Batak people and also the beauty and natural charm of Lake Toba. So, this study provides a complete review of the semiotic analysis of the film The Heart of Toba with the image of Lake Toba as a beautiful country, a piece of heaven. This research uses a semiotic approach with a qualitative research paradigm. This method is used to determine the semiotic meaning of the symbols contained in this film as a promotional film for the beauty of Lake Toba, analysis of criteria for the beautiful land of pieces of paradise, and the correlation of The Heart of Toba film with branding of Lake Toba, the beautiful land of pieces of paradise. Semiotic analysis tries to reveal the signifier and the signified as well as the meaning of the film The Heart of Toba. The theoretical framework used is a semiotic approach, namely the science that examines signs in human life, the meaning obtained from a sign at the mimetic level cannot be used to express its meaning. The results of this research will be published in an accredited international journal.